Reducing emissions of a large bore two stroke cycle engine using a natural gas and hydrogen mixture - Van Norden, Vincent Ray (Kansas State University, 2008)
The United States Environmental Protection Agency (EPA) continues to tighten pollutant emission regulations throughout the United States. As a result, the need to reduce air pollutants such as nitrogen oxides (NO[subscript]x) and carbon monoxide (CO) remains a challenge for pipeline operators. NO[subscript]x formation is primarily a function of in-cylinder combustion temperatures. A challenge for engine researchers is to identify methods to lower combustion temperatures while maintaining complete combustion. Blending hydrogen into an engine's fuel can lower in-cylinder combustion temperatures and reduce pollutant emissions. Hydrogen has a wider flammability range in comparison to natural gas, which allows for leaner engine operation and lower combustion temperatures. Specifically, the very high molecular diffusivity of hydrogen creates a more uniform mixture of fuel and air. Hydrogen also has very low ignition energy, which translates into easier combustion. This paper presents test results of using hydrogen as a fuel additive for a large bore, two stroke cycle, single cylinder, natural gas fueled Ajax engine in a test laboratory. The engine was first operated at the test point on pure natural gas and allowed to stabilize. Then a mixture of hydrogen and natural gas at various molar percentages was introduced. The engine was operated entirely on the blended fuel without a pre-combustion chamber first. Next, a pre-combustion chamber was installed and the blended fuel was supplied to it while the main combustion chamber operated on pure natural gas. Engine and emissions data were recorded and physical observations were also noted, such as engine misfires. Results showed that the addition of hydrogen into the fuel gas without the use of a pre-combustion chamber reduced emissions. The addition of the pre-combustion chamber reduced NO[subscript]x emissions without the use of hydrogen. For both configurations, the engine ran smoother with no noticeable increase in misfires or detonation. The pollutant emission reduction and engine combustion stability suggest that hydrogen as a fuel additive would be a good method to meet emissions requirements.
Keywords: Hydrogen Addition; Two Stroke Cycle; Emissions; Engineering, Mechanical (0548)